African Swine Fever Virus MGF360-14L Negatively Regulates Type I Interferon Signaling by Targeting IRF3 - Wang, Yang; Cui, Shuai; Xin, Ting; Wang, Xixi; Yu, Hainan; Chen, Shiyu; Jiang, Yajun; Gao, Xintao; Jiang, Yitong; Guo, Xiaoyu; Jia, Hong; Zhu, Hongfei (Frontiers in Cellular and Infection Microbiology, 2022)
African swine fever (ASF) is a devastating infectious disease caused by African swine fever virus (ASFV). The ASFV genome encodes multiple structural and non-structural proteins that contribute to evasion of host immunity. In this study, we determined that the viral non-structural protein MGF360-14L inhibits interferon-β (IFN-β) promoter activity induced by cGAS-STING signaling. MGF360-14L was also found to downregulate expression of the IRF3 protein and promote its degradation through ubiquitin-meditated proteolysis. Moreover, MGF360-14L was shown to interact with and destabilize IRF3 by facilitating E3 ligase TRIM21-mediated K63-linked ubiquitination of IRF3. Overall, our study revealed that MGF360-14L promotes degradation of IRF3 through TRIM21, thereby inhibiting type I interferon production. These findings provide new insights into the mechanisms underlying ASFV immune evasion.